Loneliness and Internet Addiction: A Correlative Analysis in the Context of Online Education among Young Adults - Mayurakshee Gangopadhyay; Poulomi Mitra; Riya Chakraborty; Bhagyasree Chakraborty; Gargi Das (UIN Sunan Gunung Djati Bandung, 2022)
Due to pandemic online education has become the only accessible process to address diverse community in education system. It also compels students to use internet with unprescribed manner which leads to several usage of it at levels that can be called as internet addiction. On the other hand online education has excluded the social interaction process to virtual platforms with changing manner and characteristics. Due to this one can find himself/herself isolated and on the other hand who is reluctant of participation can find he/she secure. Thus with different dimensions of loneliness and a growing amount of internet addiction, the present study aims to find the primary relation between these two variables.